2001
DOI: 10.1023/a:1011964306510
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Twenty-three Fusarium culmorum and 21 F. graminearum isolates were studied for their ability to produce mycotoxins and other secondary metabolites. The strains were cultivated on rice, and the extracts analysed by gas chromatography mass spectrometry (GC-MS) after derivatization with pentafluoropropionic (PFP) reagent. Two F. culmorum strains formed nivalenol and its acetylated derivatives (chemotype II), while all F. graminearum and the other F. culmorum isolates produced deoxynivalenol (DON) via 3-acetyldeox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Culmorin and its hydroxylated congeners, but not isoculmorin, are widely distributed in various terrestrial Fusarium species, commonly found as pathogens on cereal crops [60,61]. Very often they co-occur with thrichotecenes such as deoxynivalenol (DON), which are also sesquiterpenes, but are characterised by a heavily rearranged and oxygenated carbon framework.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…Culmorin and its hydroxylated congeners, but not isoculmorin, are widely distributed in various terrestrial Fusarium species, commonly found as pathogens on cereal crops [60,61]. Very often they co-occur with thrichotecenes such as deoxynivalenol (DON), which are also sesquiterpenes, but are characterised by a heavily rearranged and oxygenated carbon framework.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…1). 7 Culmorin analogues have been shown to contribute to the cytotoxicity of F. graminearum and F. culmorum cultures, but their importance as natural pollutants of feed and food is presently unknown 8…”
mentioning
confidence: 99%
“…3 F. culmorum isolates produced more 5-hydroxyculmorin and 15-hydroxyculmorin than culmorin, whereas F. graminearum isolates produced more culmorin than 5-hydroxyculmorin and 12-hydroxyculmorin. 3 In wild-type F. graminearum 9F1, the presence of 5-, 12-, and 15-hydroxyculmorin, detectable in the extracted ion chromatogram (EIC) ( Figure 4B), was dwarfed by the high abundance of culmorin (2) ( Figure 4A), suggesting that in this strain the Clm2-encoded CYP450 displayed superior enzymatic activity to the unidentified, possibly promiscuous C-5, C-12, and C-15 oxygenases. Assuming Clm2 encodes an exclusive CYP450 oxygenase, its disruption would leave the possibly nonspecific C-5, C-12, and C-15 oxygenases fully functional and still able to hydroxylate longiborneol.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Figure 1B shows the Southern analysis of the 11 transformants using both the 5′ and 3′ gene flanking sequences as probes. Only the six ΔClm2 disruptants numbered 3,5,11,17,18, and 20 and the control C, which exhibited a simple banding pattern, were used in further analyses. We used the disruptant strain ΔClm2D20 to generate 23 add-back strains in which the entire Clm2 gene plus ∼1 kb upstream and 550 bp downstream of the gene were inserted into the genome (confirmed by PCR and Southern analysis; data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 99%